3-D Ultrasound Guidance of Autonomous Robot for Location of Ferrous Shrapnel - Rogers, Albert J. (2009)
Vibrations can be induced in ferromagnetic shrapnel by a variable electromagnet. Real time 3-D color Doppler ultrasound located the induced motion in a needle fragment and determined its 3-D position in the scanner coordinates. This information was used to guide a robot which moved a probe to touch the shrapnel fragment.